Meningkatkan Kompetensi Sumber Daya Manusia Dengan Disiplin Kerja Sebagai Variabel Moderasi Dalam Pencapaian Kinerja Pegawai Badan Pengelolaan Keuangan dan Aset Daerah Provinsi Lampung - Mustakim, Senen; Parela, Epi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to determine the influence of HR competencies and work discipline on employee performance at the Regional Financial and Asset Management Agency of Lampung Province and test the influence of HR competencies on employee performance with work discipline as a moderation variable. The research carried out is quantitative research. The data source used is primary data distributed to employees of the Lampung Provincial Regional Financial and Asset Management Agency. This study used 35 research respondents. There are three variables in this study, namely: 1 (one) independent variable (X), 1 (one) moderating variable (M) and employee performance (Y) as a bound variable. From the results of data processing, hypothesis answers have been found, which are as follows; competency variable (X) has no effect on employee performance (Y). The variable of work discipline (M) affects employee performance (Y) and work discipline strengthens the influence of competence (X) on employee performance (Y) at the Regional Financial and Asset Management Agency of Lampung Province. The results of this study provide strategic recommendations for government organizations to not only focus on training and upskilling employees, but also build systems that encourage and maintain work discipline. That way, the achievement of employee performance can be maximized in a sustainable manner, which ultimately supports the improvement of the quality of public services and better regional financial management
Keywords: Human Resources Competence; Work Discipline; and Employee Performance